Diab selects SABIC's LNP™ COLORCOMP™ compound to enhance wind turbine foams. Issue 3 (March 2021) - Unknown
Abstract : Diab Group, a leader in sandwich composite solutions, chose SABIC's new LNP™ COLORCOMP™ compound using nanotechnology to reduce weight and improve mechanical properties of sandwich structures made with polyethylene terephthalate (PET) foams used as the core material of wind turbine blades.